MANCHESTER CLINICAL PLACEMENT INDEX (MCPI) AS CLINICAL LEARNING ENVIRONMENT ASSESSMENT TOOL: ADAPTATION INTO INDONESIAN LANGUAGE - Carolyn Carolyn; Arnold Lukito; Audelia Kathleen Sulaiman; Elisabeth Rukmini (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: Clinical Learning Environment (CLE) involves many active dynamics, perceptions construction, learners' experiences, and behavior while learning. It includes every human resource working and learning together, a health system, and communities. Standard assessment of CLE is essential to evaluate CLE. The Manchester Clinical Placement Index (MCPI) assesses the CLE based on Community of Practice Theory, emphasizing learning according to experience-based learning. Translation of the MCPI into the Indonesian language will be valuable to assess the CLE. This research intends to translate and adapt MCPI into the Indonesian language. Therefore, MCPI can be used to assess the CLE in Indonesian medical schools.Methods: An expert panel translated the MCPI into the Indonesian language (I-MCPI), and a language learning center validated the translation. Participants who were final year students (N: 155) filled up the online I-MCPI after the informed consent. To assess the I-MCPI validity, we performed exploratory factor analysis (EFA) and item discrimination. To seek reliability, we utilized internal consistency reliability showing as the Cronbach's alpha coefficient.Results: The factor analysis and item discrimination showed the I-MCPI's validity. We found two subscales similar to the original MCPI. Leadership, reception, people, facilities, and organization have similar correlation strength to Subscale Learning Environment (0.60-0.71). Instruction and observation have similar correlation strength to Subscale Training (0.86-0.89). Subscale feedback correlates less than 0.60 for both subscales; thus, we concluded that feedback went to the subscale Training as the original MCPI. Reliability of the I-MCPI showed an excellent internal consistency with Cronbach's alpha of 0.87.Conclusion: I-MCPI is a valid and reliable tool to assess the CLE. Further research with broader cohorts of medical schools will be valuable for advancing medical education in Indonesia.